Determinants and prognostic value of Galectin-3 in patients with aortic valve stenosis. Issue 11 (19th February 2016) - Arangalage, Dimitri; Nguyen, Virginia; Robert, Tiphaine; Melissopoulou, Maria; Mathieu, Tiffany; Estellat, Candice; Codogno, Isabelle; Huart, Virginie; Duval, Xavier; Cimadevilla, Claire; Vahanian, Alec; Dehoux, Monique; et al.
Abstract : Objective: Myocardial fibrosis has been proposed as an outcome predictor in asymptomatic patients with severe aortic stenosis (AS) that may lead to consider prophylactic surgery. It can be detected using MRI but its widespread use is limited and development of substitute biomarkers is highly desirable. We analysed the determinants and prognostic value of galectin-3, one promising biomarker linked to myocardial fibrosis. Methods: Patients with at least mild degenerative AS enrolled between 2006 and 2013 in two ongoing studies, COFRASA/GENERAC (COhorte Française de Rétrécissement Aortique du Sujet Agé/GENEtique du Rétrécissement Aortique), aiming at assessing the determinants of AS occurrence and progression, constituted our population. Results: We prospectively enrolled 583 patients. The mean galectin-3 value was 14.3±5.6 ng/mL. There was no association between galectin-3 and functional status (p=0.55) or AS severity (p=0.58). Independent determinants of galectin-3 were age (p=0.0008), female gender (p=0.04), hypertension (p=0.002), diabetes (p=0.02), reduced left ventricular ejection fraction (p=0.01), diastolic dysfunction (E/e′, p=0.02) and creatinine clearance (p<0.0001). Among 330 asymptomatic patients at baseline, galectin-3 was neither predictive of outcome in univariate analysis (p=0.73), nor after adjustment for age, gender, rhythm, creatinine clearance and AS severity (p=0.66). Conclusions: In a prospective cohort of patients with a wide range of AS severity, galectin-3 was not associated with AS severity or functional status. Main determinants of galectin-3 were age, hypertension and renal function. Galectin-3 did not provide prognostic information on the occurrence of AS-related events. Our results do not support the use of galectin-3 in the decision-making process of asymptomatic patients with AS. Trial registration number: COFRASA NCT00338676 and GENERAC CT00647088